Public food procurement as a game changer for food system transformation - Swensson, Luana; Hunter, Danny; Schneider, Sergio; Tartanac, Florence (Food and Agriculture Organization of the United Nations, 2021)
In the last decade various countries, regions and cities from low-income to high-income economies have been developing Public Food Procurement (PFP) initiatives designed to use government purchasing power and regular demand for food as a policy instrument to promote sustainable development. These initiatives – often referred also as institutional food procurement - include school feeding or school meals programmes , as well as the purchase of food for public hospitals, prisons, universities, public building’s cafeterias, and other social programmes. These initiatives have been increasingly recognised also as an important game changer and entry point to trigger more sustainable food systems and healthy diets.